2011
DOI: 10.1590/s1415-43662011000300014
|View full text |Cite
|
Sign up to set email alerts
|

Modificação das propriedades das fibras de curauá por acetilação

Abstract: RESUMONos compósitos cimentíceos as fibras vegetais podem sofrer vários graus de degradação quando expostas ao ambiente alcalino. O meio alcalino degrada os componentes macromoleculares das fibras, principalmente pela solubilização da lignina e a desfibrilação da celulose, comprometendo suas propriedades físicas e mecânicas. A resistência das fibras vegetais ao ataque alcalino pode ser aumentada por meio de tratamentos químicos superficiais como a acetilação que apresenta capacidade de reduzir a natureza higro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
(4 reference statements)
0
2
0
6
Order By: Relevance
“…This indicates no significant changes in the chemical structure of the residue exposed to to the alkaline environment. The work of Wang et al (2016) also submitted cellulosic cotton residue to an alkaline treatment based on NaOH and NaOH/Urea, and also confirmed that no chemical reaction occurred during alkaline treatment[14,23,24].…”
mentioning
confidence: 87%
“…This indicates no significant changes in the chemical structure of the residue exposed to to the alkaline environment. The work of Wang et al (2016) also submitted cellulosic cotton residue to an alkaline treatment based on NaOH and NaOH/Urea, and also confirmed that no chemical reaction occurred during alkaline treatment[14,23,24].…”
mentioning
confidence: 87%
“…Cai et al, 2019;Gorgulho et al, 2018;Hospodarova et al, 2018;Hu et al, 2019).After acetylation treatment, variations were observed in the couplings of characteristic bands; a reduction of the hydroxyl groups (O-H) occurs, which can be evidenced by decrease in absorption intensity in the reference band. Successful esterification can be confirmed by the behavior of three important absorption bands around 1736, 1367, and 1242 cm -1 , related to stretching vibration in carbonyl C = O, C -H, and C-O(Behnood et al, 2016;Gorgulho et al, 2018;Lopes et al, 2010b;Sun et al, 2004).…”
mentioning
confidence: 88%
“…O valor de umidade apresentado pela fibra apenas lavada é inferior a 10%, enquanto o apresentado pela fibra tratada com NaOH foi superior a 30%[34], como mostra a Figura 4. De acordo com[37], este resultado acontece, pois o tratamento alcalino promove uma maior remoção dos constituintes presentes e isto permite que a fibra absorva uma quantidade muito superior de umidade, já que uma das características da fibra natural é sua capacidade higroscópica. Figuras 5 apresenta as curvas de fusão do PHB puro e dos seus compósitos biodegradáveis contendo 10 e 30% em massa de fibra de piaçava tratada com NaOH.…”
unclassified